Employee participation in governance : a legal and ethical analysis / Michael Lower. - Lower, Michael associate professor (Cambridge University Press, 2010)
The rights of the employee and the themes of employee ownership and participation have been central, recurring themes as the body of Catholic Social Thought has developed. There is now a unified corpus of official Catholic teaching that focuses the resources of moral theology and natural law theory on the important social issues of the day such as this. The description and explanation of the essential elements of Catholic Social Thought and its relationship to these themes helps the reader think about the place of the corporation in the economy and whether British and European corporate governance and labour law do what they should to put the employee at the centre of corporate governance.